Effect of precipitating agents for the preparation of Fe-based catalysts on coal pyrolysis: Effect of Ba and Mg additives. (15th July 2022) - Deng, Jin; Deng, Xiaoling; Yuan, Shenfu; Ma, Duo; Liu, Jiajia; Xie, Xiaoguang; He, Renze; Yang, Tai
Highlights: The precipitating agent affected the activity of Fe catalyzed coal pyrolysis. Fe catalyst (Fe-X4) prepared with KOH showed the best catalytic activity. Mg and Ba prevented the combination of Si and Fe in coal to form Si-O-Fe. Abstract: In this work, the effect of Fe catalysts prepared with four precipitating agents (ammonia, urea, KOH and NaOH) on the catalytic pyrolysis of coal (BC) was investigated using a fixed-bed reactor under 0.1 MPa N2 and 700 °C. The results indicated that the precipitating agent significantly affected the activity of the Fe catalyst (5 wt%). Concretely, the Fe catalysts obtained with ammonia (Fe-X1) and urea (Fe-X2) as precipitating agents showed low activity was attributed to the small size of the particles blocked the pores of the coal, making it difficult for Fe species to be reduced. The Fe catalysts obtained with NaOH (Fe-X3) and KOH (Fe-X4) as precipitating agents showed good catalytic activity. However, the final metal Fe phase in Fe-X3 catalyst had a large particle size and aggregation. The Fe-X4 catalyst facilitated the preferential consumption of small defective structures and the removal of small aromatic rings, and the catalyst particles were uniformly dispersed and showed the best catalytic activity. Accordingly, the Fe-X4 catalyst had the highest total conversion (56.79 wt%) and H2 yield (93.66 ml/g) in coal pyrolysis. Moreover, Mg and Ba enhanced the activity of the Fe catalyst, which was attributed to the fact that Mg and Ba promoted the dispersion of Fe and prevented the formation of Fe-O-Si from the original Si in the coal, and the effect of Mg was greater than that of Ba.